Assessing the Efficacy of Internal Control and its Influence on Financial Performance: Evidence from Iraqi Telecommunications Corporation - Khlaif, Murtadha Hasan; Farhan, Raghad Mounir; Wahhab, Asaad (Technium Social Sciences Journal, 2025)
Effective internal control serves as a safeguard for global firm projects. It safeguards their assets from depletion and mismanagement while ensuring the enduring sustainability of enterprises through prudent strategic choices. This study seeks to evaluate the impact of adequate internal controls on the financial performance of Iraqi telecommunications companies. The survey includes three telecommunications companies: Zain Iraq, Asia Cell, and Korek. Due to Korek’s closure in 2024, the study sample was picked from Zain Iraq and Asiacell. To achieve the study’s objectives and answer its questions, we gathered data on the financial performance of the companies investigated from financial statements issued on the Iraq Stock Exchange for 2018-2023. Data on the most frequently utilized performance indicators in the strategic decision-making process were examined. Audited financial statements for the years 2018-2023 were analysed using the most prevalent financial analysis ratios to assess the efficacy of internal control. The study found that financial analysis indicators reflect the effectiveness of internal control in Iraqi telecommunications businesses in 2023. However, it failed frequently between 2019 and 2021, which might be attributed to the COVID-19 epidemic and the following economic impact on all enterprises in other countries worldwide.